The Apoptotic Mechanism of Action of the Sphingosine Kinase 1 Selective Inhibitor SKI-178 in Human Acute Myeloid Leukemia Cell Lines - Dick, Taryn E. (J Pharmacol Exp Ther, 2015)
We previously developed SKI-178 (N′-[(1E)-1-(3,4-dimethoxyphenyl)ethylidene]-3-(4-methoxxyphenyl)-1H-pyrazole-5-carbohydrazide) as a novel sphingosine kinase-1 (SphK1) selective inhibitor and, herein, sought to determine the mechanism-of-action of SKI-178–induced cell death. Using human acute myeloid leukemia (AML) cell lines as a model, we present evidence that SKI-178 induces prolonged mitosis followed by apoptotic cell death through the intrinsic apoptotic cascade. Further examination of the mechanism of action of SKI-178 implicated c-Jun NH(2)-terminal kinase (JNK) and cyclin-dependent protein kinase 1 (CDK1) as critical factors required for SKI-178–induced apoptosis. In cell cycle synchronized human AML cell lines, we demonstrate that entry into mitosis is required for apoptotic induction by SKI-178 and that CDK1, not JNK, is required for SKI-178–induced apoptosis. We further demonstrate that the sustained activation of CDK1 during prolonged mitosis, mediated by SKI-178, leads to the simultaneous phosphorylation of the prosurvival Bcl-2 family members, Bcl-2 and Bcl-xl, as well as the phosphorylation and subsequent degradation of Mcl-1. Moreover, multidrug resistance mediated by multidrug-resistant protein1 and/or prosurvival Bcl-2 family member overexpression did not affect the sensitivity of AML cells to SKI-178. Taken together, these findings highlight the therapeutic potential of SKI-178 targeting SphK1 as a novel therapeutic agent for the treatment of AML, including multidrug-resistant/recurrent AML subtypes.